‘TONE AT THE TOP’: FIGHTING MILITARY CORRUPTION IN LATIN AMERICA - Klaus, Liliane (Scientia Militaria - South African Journal of Military Studies, 2015)
This essay aims to discuss how tone at the top works in the traditional military contexts found in Latin America, and how the right tone could be adopted in corrupt military institutions to move towards an ethical role-modelling environment. For this endeavour, several strategies that can help military generals to fight military unethical culture in contaminated hierarchical organisations will be proposed, while a number of hypotheses on the institution’s functioning will be provided. Differently from private companies’ theoretical bias, the main suggested approach implies the initial establishment of a strong, transactional-based tone at the top as the main tool to fight military corruption. As a further step, after the corrupt culture has been neutralised, transactional leadership based on ethics could be slowly transformed into gentler versions of transformational style, but never letting the main fear of the harshest punishment evanesce. In summary, by showing that unethical leadership will necessarily pave the way for misconduct in traditional military organisations, we propose a cannonball strategy, based on a punishment and reward system, to reinforce integrity instead of gentler or charismatic leadership styles.